Digitalization as a way to promote the holistic approach to faculty development: a developmental evaluation - Silva, Roberta (Frontiers in Education, 2023)
Faculty Development, in the last decades, has undergone many transformations and many scholars are now wondering what will be the main feature that will characterize the next age, an age distinguished, in the academic world, by the changes that the just experienced pandemic brought with it. One of the main changes that this pandemic has brought with itself is the increase in digitalization within academic institutions and, consequently, the increase in the number of Faculty Development proposals that are conveyed through online initiatives. However, this is a consideration that can be read not only as a stand-alone element but, if properly contextualized, it could be used as a way to promote Faculty Development programs that exploit the potential offered by digitalization in order to create initiatives which are linked in a mutually reinforcing bond. This choice is consistent with the adherence to a holistic approach to Faculty Development that promotes a systemic and multifocal logic.Mary Deane Sorcinelli (Sorcinelli et al, 2006;Sorcinelli, 2020) has presented an evolution of the concept of Faculty Development organized for "Ages" according to which a) the Sixties were "The Age of Scholar" in which the primary purpose of Faculty Development was to support faculty members in the development of their academic skills within their disciplines; b) the Seventies were "The Age of Teacher" in which academic institutions focused their attention on the development of their staff's teaching skills; c) the Eighties were "The Age of Developer" in which the role of faculty developers was officially recognized; d) the Nineties were "The Age of the Learner" in which more and more programs of Faculty Development were focused on promoting a more autonomous and active learning process (also through the spread of digital technologies supporting learning); e) the beginning of the 21st century was "The Age of the Network" in which, even through the use of digital platforms, academic institutions all over the world started an enriching confrontation about their Faculty